2019
DOI: 10.1149/2.0331907jes
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Microstructure Reconstruction of a Binder/Carbon Fiber/Expanded Graphite Carbon Fiber Paper for PEMFCs Applications: Mass Transport and Conductivity Properties

Abstract: Mass transport and conductivity properties of the carbon fiber papers (CFPs) used in gas diffusion layers are among the critical parameters that affect a proton exchange membrane fuel cell (PEMFC) performance. Here, instead of carbonization/graphitization in the commercial CFPs manufacturing steps, the expanded graphite (EG) is numerically added to the CFP substrate to compensate and enhance the conductivity. The microstructures of different polymer binder/carbon fiber (CF) composites with and without EG are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Based on available data in the literature and online by the manufacturer (Bekaert), the typical porosity of Ti felt PTLs is in the range of 0.40–0.90, the fiber diameter 10 μm–50 1.69998pt1.69998ptμnormalm ${{\rm { \hskip0.17em\hskip0.17em{\rm \mu} m}}}$ , and the thickness 100 μm–2 mm ${{\rm { mm}}}$ [9,10] . To generate the virtual PTLs with customized structures, a stochastic reconstruction algorithm implemented in MATLAB R2021b was applied, based on well‐described methods from literature [53–55] . Figure 2b shows the flow chart of the generation of a titanium felt‐based PTL within this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on available data in the literature and online by the manufacturer (Bekaert), the typical porosity of Ti felt PTLs is in the range of 0.40–0.90, the fiber diameter 10 μm–50 1.69998pt1.69998ptμnormalm ${{\rm { \hskip0.17em\hskip0.17em{\rm \mu} m}}}$ , and the thickness 100 μm–2 mm ${{\rm { mm}}}$ [9,10] . To generate the virtual PTLs with customized structures, a stochastic reconstruction algorithm implemented in MATLAB R2021b was applied, based on well‐described methods from literature [53–55] . Figure 2b shows the flow chart of the generation of a titanium felt‐based PTL within this work.…”
Section: Methodsmentioning
confidence: 99%
“…[9,10] To generate the virtual PTLs with customized structures, a stochastic reconstruction algorithm implemented in MATLAB R2021b was applied, based on well-described methods from literature. [53][54][55] Figure 2b shows the flow chart of the generation of a titanium felt-based PTL within this work. In order to customize the structural characteristics of stochastically generated PTLs, the PTL structural parameters need to be input in the code, including matrix domain size, porosity, fiber radius, fiber length, and anisotropy parameter.…”
Section: Methodology Stochastically Numerical 3-d Structure Reconstru...mentioning
confidence: 99%
“…Carbon fiber paper is the most widely used material for MPS due to its ease in shaping a thin layer with a uniform porous structure, its high electrical/thermal conductivity and its excellent chemical/thermal stability [34][35][36]. The carbon fibers used in MPS are generally 5-15 µm in diameter, and the thickness of the carbon fiber paper thereby prepared typically has a thickness within 200-400 µm and an average pore size of tens of micrometers [37][38][39].…”
Section: Carbon Fiber Papermentioning
confidence: 99%
“…As the temperature of the carbon fiber production process increases, the concentration of structural defects is reduced and crystal order is improved [ 21 ], which results in increased thermal conductivity. Recent studies on commercially available polyacrylonitrile (PAN)-based carbon fibers have shown that, at room temperature, the thermal conductivity of the fibers along their axis ranges from about 5 up to 156 W·m −1 ·K −1 [ 22 , 23 ]. The thermal conductivity values of carbon fibers based on regenerated cellulose (Rayon) along the axis have been found to be in the range of 5 to 15 W·m −1 ·K −1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%